Reassessing Sovereignty and Sustainability in Nickel Downstreaming: An Economic Analysis of Indonesia’s Legal Framework - Endrianto Bayu Setiawan; Imam Koeswahyono; Indah Dwi Qurbani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Indonesia possesses the world’s largest nickel reserves, positioning the commodity as a key strategic natural resource—often classified as a critical mineral. Based on Article 33 of the 1945 Constitution, the governance of natural resources, including nickel, must be carried out fairly and sustainably to benefit the people's welfare. The policy of nickel downstreaming, particularly through the development of smelter industries, represents one expression of state sovereignty over natural wealth. Nonetheless, the execution of this policy presents several challenges, including environmental degradation, unequal distribution of economic gains, and reliance on non-renewable, polluting energy sources like coal. This study adopts an economic analysis of law framework to evaluate the efficiency and effectiveness of Indonesia’s nickel downstreaming regulations. Using a normative juridical method with statutory and conceptual approaches, the research finds that although current regulations formally demonstrate state sovereignty, they fall short in upholding the constitutional principles of sustainability and social justice. The policy has, in practice, led to environmental harm and socio-economic disparities among impacted communities. From an economic analysis of law perspective, the downstreaming strategy has yet to achieve optimal economic efficiency, fair benefit distribution, and proper handling of negative externalities. As such, regulatory reform is essential to ensure legal certainty, promote environmental preservation, and reinforce social welfare through mining downstream policies, including those related to nickel.